The Los Angeles riots: lessons for the urban future - Baldassare, Mark (Urban policy challenges, 1994)
Introduction / Mark Baldassare -- A riot of color : the demographic setting / Peter A. Morrison and Ira S. Lowry -- Los Angeles coalition politics / Raphael J. Sonenshein -- The Rodney King beating verdicts / Hiroshi Fukurai, Richard Krooth, and Edgar W. Butler -- Public opinion before and after a spring of discontent / Lawrence Bobo ... [et al.] -- A profile of those arrested / Joan Petersilia and Allan Abrahamse -- Property damage and violence : a collective behavior analysis / Kathleen J. Tierney -- Black-Korean conflict / Regina Freer -- Community coalition-building / James A. Regalado -- Urban rioting in Los Angeles : a comparison of 1965 with 1992 / David O. Sears